POD DAMAGE MODELING AND FORECASTING IN EARLY MATURING PIGEONPEA ( TURING PIGEONPEA (Cajanus cajan) Cajanus cajan) FOR CENTRAL ZONE (CZ) FOR CENTRAL ZONE (CZ) OF INDIA - PRITY KUMARI; G. C. MISHRA (The Bioscan, 2018)
The present investigation was aimed to compare the ability of Autoregressive Integrated Moving Average (ARIMA), Exponential smoothing and Neural network (NN) model for forecasting percent pod damage by pod borer in early maturing pigeonpea yield grown in central zone of India. Based on studies, neural network was found to be more suitable for predicting pigeonpea yield as compared to two other models.